(untitled) (The Batuk, 2024)
The issue of women empowerment is a significant focus in developing countries as it has a high potential for poverty reduction and overall development. Microfinance institutions (MFIs) have emerged as potential instruments for addressing both poverty and women’s empowerment. This study investigated the connection between microfinance and women’s empowerment in rural Nepal. Through a survey among 150 women clients of MFIs in Rautahat district, the study analyzed how social empowerment of women changes after participation is microfinance programs. Employing hypotheses testing with statistical tests like the Wilcoxon Signed Rank Test and One-sample t-test, the study found compelling evidence of a positive influence of microfinance on women’s empowerment. After participation in microfinance programs, women’s status was found significantly increased in terms of ownership in assets, decision-making autonomy, freedom of mobility and social recognition. These findings suggest that microfinance can be a valuable tool for empowering women in developing countries, potentially leading to improved social well-being, and increased participation in community decision-making. However, further research is needed to understand the long-term sustainability of these impacts and address potential challenges such as debt burden and social stigma associated with borrowing.